Optimizing the Strategic Application of Management Science: An Urban Case Study for the Sustainability of MSMEs in Bintaro, South Tangerang City - Windarko, Windarko (IJBLE Scientific Publications Community Inc., 2024)
The objective of this study is to explore the most effective ways to apply Management Science strategically within Micro, Small, and Medium Enterprises (MSMEs/UMKM) located in the Bintaro area of South Tangerang City, West Java, Indonesia. Through a combination of mathematical analysis and technology utilization in a case study framework, the research evaluates the management science strategies employed by MSMEs in Bintaro and their effects on business performance and sustainability. The outcomes of this investigation are anticipated to offer valuable perspectives for stakeholders, business professionals, and scholars aiming to enhance MSME management techniques for better outcomes.